Meningkatkan Kemampuan Menulis Kreatif Untuk Siswa SMK Labor Pekanbaru - Muhammad Kafrawi; Evizariza (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2022)
Writing skills are an important part of today's era. Along with the development of technology, the ability to write becomes a force to disseminate useful and useful information to the general public. By writing, the author can issue ideas or ideas through written language. In addition, writing is able to arouse creativity, sharpen the imagination of the younger generation, especially students. Aside from being a medium for expressing ideas or ideas, writing also shapes the character of students by directing the creative potential obtained from reality. Improving Creative Writing Skills aims to produce reliable young writers for Riau Province in the future.